What contribute to the formation of learning organization? A study of organization citizenship behavior and personality traits among organization’s employees / Mastura Ab Ghani - Ab Ghani, Mastura (Faculty of Business and Management, 2010)
Interest in learning organization has already increased over the past decades. Learning organization is viewed as a mean for long term success. Therefore, organizations need to be identifying what behavior and personality contributes to the formation of learning organization in the organization. For this research study, the researcher use dimension of Organizational Citizenship Behavior and also dimension of Personality Traits (Big Five Personality Traits) as to investigate whether these factors contribute to the formation of learning organization. The main objective of this research is to determine whether dimension of Organizational Citizenship Behavior contribute to the development of learning organization. Beside that, the second objective is to determine whether all dimensions of Personality Traits contribute to the development of learning organization. Researcher used questionnaire as a main instrumental in data collection method. For this research, the researcher achieved to collect 318 respondents from 7 different companies. From the findings, the researcher also gives some recommendations for the organization and future researcher. After data have been collected, it will be analyzed using frequency, percentage, mean, standard deviation, Pearson Correlation and Regression. From the findings, the researcher also gives some recommendations for the organization and future researcher.